2019
DOI: 10.1093/bjc/azz016
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant Perceptions of the Police: The Role of Country of Origin and Length of Settlement

Abstract: Relationships between police and minority groups have been shown to be strained with members of these groups often viewing police in a more negative light. Distinguishing between minority group and immigrant populations, more recent work has shown that foreign-born individuals are more likely to view the police in a more favourable light than native-born populations. Adding to this literature, we examine group-specific factors that shape foreign-born individuals’ views of the police. We find that country of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…However, upon including measures of police contact, group position (i.e., social inclusion), and changes in institutional frames, the relationship between immigration status and perceptions of police legitimacy was insignificant, suggesting that the relationship between immigration status and attitudes toward police is complex. Recent work by Jung et al (2019) extended this line of research by showing that type of government of the country of origin and recency of immigration interact in predicting perceptions of police officers. Collectively, this work provides partial support for Wu et al’s (2017) theoretical framework by showing that a host of situational characteristics and contextual factors, pre-and post-arrival, influence the relationship between immigration status and perceptions of police.…”
Section: Immigration and Perceptions Of The Policementioning
confidence: 95%
See 3 more Smart Citations
“…However, upon including measures of police contact, group position (i.e., social inclusion), and changes in institutional frames, the relationship between immigration status and perceptions of police legitimacy was insignificant, suggesting that the relationship between immigration status and attitudes toward police is complex. Recent work by Jung et al (2019) extended this line of research by showing that type of government of the country of origin and recency of immigration interact in predicting perceptions of police officers. Collectively, this work provides partial support for Wu et al’s (2017) theoretical framework by showing that a host of situational characteristics and contextual factors, pre-and post-arrival, influence the relationship between immigration status and perceptions of police.…”
Section: Immigration and Perceptions Of The Policementioning
confidence: 95%
“…The literature on immigrants’ perceptions of the police is limited (Bradford & Jackson, 2018; Jung et al, 2019; Weitzer, 2014) and relatively atheoretical in nature (Wu et al, 2017), and has produced mixed results. For instance, some studies have found that immigrants to report more positive perceptions of the police than non-immigrants (Correia, 2010; Davis & Hendricks, 2007; Rengifo & Fratello, 2015; Wortley & Owusu-Bempah, 2009).…”
Section: Immigration and Perceptions Of The Policementioning
confidence: 99%
See 2 more Smart Citations
“…As race, ethnicity and immigration are closely intertwined, it is worthwhile to briefly review research on the relationship between immigrant status and perceptions of police (Jung et al. , 2019; Wu, 2010; Choi, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%